A Multicenter Analysis of the Outcome of Cancer Patients with Neutropenia and COVID-19 Optionally Treated with Granulocyte-Colony Stimulating Factor (G-CSF): A Comparative Analysis - Sereno, María; Jiménez Gordo, Ana María; Baena Espinar, Javier; Aguado, Carlos; Mielgo Rubio, Xabier; Pertejo, Ana; Álvarez Álvarez, Rosa; Sánchez, Ana; López, Jose Luis; Molina, Raquel; López Alfonso, Ana; Hernández, Berta; et al. (My University, 2021)
Infections with COVID-19 in neutropenic cancer patients are related to poor outcomes. A G-CSF treatment used in neutropenic cancer with SARS-CoV-2 infections is related to a higher rate of respiratory failure according to progressive and growing evidence. In this small retrospective non-randomized study, we found an association between G-CSF treatment and the parameters predisposing for worse infections with COVID-19 and neutropenia compared with patients not treated with G-CSF. We also found that the number of days on G-CSF treatment was related to a higher risk of mortality in a multivariable analysis among patients treated with G-CSF.